Reformulation of Decision-making System in ASEAN - Syofyan, Ahmad; Azizah, Siti; Akayleh, Shaker Suleiman Ali Al; Panjaitan, Oksha Dwi Anugrah; Kusworo, Daffa Ladro (Faculty of Law, Hasanuddin University, 2023)
ASEAN is a regional organization for Southeast Asia that was established on 8 August 1967 by five ASEAN countries at the time, namely Indonesia, Singapore, Malaysia, Thailand and the Philippines. Today, ASEAN has eleven members with Timor Leste as the youngest member. Like any other international organization, ASEAN has its own decision-making system. The decision-making system in ASEAN before the Charter was only consultation and consensus. That is, decision making based on the agreement of all members and can only be decided if no one refuses, this refers to the Bangkok Declaration. Meanwhile, after the establishment of the 2007 ASEAN Charter, there is a new decision-making system, namely ASEAN Minus-X. A decision-making system that does not rely on the approval of all its members, so that a policy can be decided even if only approved by a few members. This decision-making system can only be done in the economic field. From these two decision-making systems, there are several challenges that exist so that new ideas emerge to reformulate the decision-making system in ASEAN, which is considered relevant to the times and can accommodate all the interests of ASEAN members.